Laser powder bed fusion of lattice structures for thermomechanical applications - Catchpole-Smith, Sam (2020)
Laser powder bed fusion (LPBF) is increasingly being adopted in high-value industries such as aerospace because of its design freedoms. An example of LPBF design freedom is incorporation of lattice structures within components. These structures exist in forms including strut-type, consisting of beam elements connected at nodes, and mathematically defined surface-based geometries, where triply periodic minimal surface (TPMS) lattices are found. Strut-type lattices have already found application in end-use components where they are typically used to reduce component mass due to their high specific strength properties. Lattice structures also show promise in heat transfer applications, but there is a lack of research in evaluating performance in this area.